Os limites entre o controlo político e a profissionalização da Administração Pública - Asensio, M. (Revista de Administração e Emprego Público, 2017)
A long-standing concernin the academic field of public administration is the role played bypoliticians and bureaucrats in the process of governance. The nature of this relationship and the appropriate role of political leaders and administrators has been the subject of considerable debate throughout the history. Therefore, the academic debateon politics-bureaucracy relations and proliferation of ideas forstriking a balance between them has been going on for centuries. The relationship between these two actors remains a central problem for responsive governance. In recent decades, the growing crisis in governance and the changes in the global context have tended to redefine the roles and relationships between politicians and bureaucrats in the process of public management. This article aims to provide an in-depth theoretical analysis by discussing the relationships between politicians and bureaucrats. A review of relevant literature will provide a brief summary of the century long scholarly debates on politics-bureaucracy. The relevant literature will be divided into four sections –accordance with the approach of classical, neo-classical, new public management and emerging trendsof politics-bureaucracy relations.The argument is developed in the following way: First, some characteristics of the classical outlookare outlined. Second, claims about the undesirability of the dichotomy are discussed. Third, aspects of new public management and administrative dynamics are inquired, fourth, a redefinition of the dichotomy is identified and finally, some reasons for rediscovering the complementarity is recapitulated.